Techniques and Methods of Deviation in the Poetry of Kazem Al-Hajjaj and Mohammed Al-Khafaji - Hameed Nassrah Al-Musaedi, Imad; Mohammadi Rakati, Danesh; Nazari, Yusuf ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2025)
This study explores the use of deviation techniques in the poetry of Kazem Al-Hajjaj and Mohammed Al-Khafaji, highlighting their stylistic and semantic innovations. Using a stylistic approach, it analyzes semantic, linguistic, and rhythmic deviations. Al-Hajjaj employs a seemingly simple yet profound style, blending everyday language with vivid imagery reflecting Iraqi life. In contrast, Al-Khafaji uses complex symbolism and abstract language to express philosophical ideas, requiring deeper reader reflection. The study shows that both poets offer unique poetic experiences, representing two distinct trends in modern Iraqi poetry: concentrated simplicity and intricate symbolism.